Erythromycin Induced Carbamazepine Toxicity- A Preventable Drug Interaction - Shrestha, Devendra; Dhakal, AK; Singh, KK (Journal of Chitwan Medical College, 2014)
A drug interaction between Erythromycin and Carbamazepine is well established and harmful effects of Carbamazepine toxicity can be avoided. We report a patient who developed features of Carbamazepine toxicity namely ataxia, vomiting and nystagmus within 24 hours of oral Erythromycin with high serum Carbamazepine level and improved after discontinuation of Erythromycin with returning of serum Carbamazepine level to therapeutic range. Awareness among health professionals, patient education, proper record keeping and strengthening pharmacy services are essential to prevent such drug interactions. Journal of Chitwan Medical College 2013; 3(4); 52-53 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9556